Pengaruh Lingkungan Belajar Dan Kreativitas Belajar Masa Pandemi Covid 19 Terhadap Hasil Belajar Ekonomi Siswa Kelas X Di SMA IT Yapira Rumpin Bogor - Siska Wahdaniyah; Surasni Surasni (Pekobis : Jurnal Pendidikan, Ekonomi, dan Bisnis, 2021)
The purpose of the study was to analyze the significant influence between the Learning Environment during the Covid-19 pandemic and learning creativity during the Covid-19 pandemic on the economics learning outcomes of class X students at SMA IT YAPIRA Rumpin Bogor. Meanwhile, the research methodology used was a quantitative approach with association methodology. The implementation of the research was carried out using initial observations to see the condition of students at SMA IT Yapira Rumpin Bogor directly, documentation in the form of economic learning outcomes through teachers in the field of study and questionnaires. Sampling was drawn at population of 60 students and using random sampling technique, then a sample of 52 students was taken. The results showed that there was a positive influence of the learning environment and learning creativity on the economics learning outcomes of class X students at SMA IT Yapira Rumpin Bogor.